2022
DOI: 10.35762/aer.2021.44.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Emissions from Cement Plants Using AERMOD Modeling

Abstract: Coal combustion generates many gases and emissions which are harmful to public health and the environment. So, it is necessary to assess the health risks for the people living in the nearby cement plants that use coal as a fuel. In this article, a health risk assessment HRA was carried out concerning the air emissions from a cement plant in the heavy industry area located at Beni Suef governorate - Egypt. The article handles the assessment of the health risks for pollutants classified as non-carcinogenic i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Abdel-Gawad et al (2022) measured and evaluated long-and short-term health impacts to predict the ground level concentration of SO 2 , mercury, arsenic, and chromium VI by using the AERMOD model within a 30 km radius of the studied cement industry. The finding revealed that meteorological data and topographical data were the important factors in predicting pollutant dispersion [60]. In Thailand, Seangkiatiyuth et al (2011) applied the model to study the environmental impact assessment of NO 2 from the cement complex.…”
Section: Mathematical Dispersion Modelingmentioning
confidence: 99%
“…Abdel-Gawad et al (2022) measured and evaluated long-and short-term health impacts to predict the ground level concentration of SO 2 , mercury, arsenic, and chromium VI by using the AERMOD model within a 30 km radius of the studied cement industry. The finding revealed that meteorological data and topographical data were the important factors in predicting pollutant dispersion [60]. In Thailand, Seangkiatiyuth et al (2011) applied the model to study the environmental impact assessment of NO 2 from the cement complex.…”
Section: Mathematical Dispersion Modelingmentioning
confidence: 99%